2011
DOI: 10.1002/chem.201102437
|View full text |Cite
|
Sign up to set email alerts
|

From {Bi22O26} to Chiral Ligand‐Protected {Bi38O45}‐Based Bismuth Oxido Clusters

Abstract: The reaction of [Bi(22)O(26)(OSiMe(2)tBu)(14)] (1) in THF with salicylic acid gave [Bi(22)O(24)(HSal)(14)] (2) first, which was converted into [Bi(38)O(45)(HSal)(22)(OH)(2)(DMSO)(16.5)]·DMSO·H(2)O (3·DMSO·H(2)O) after dissolution and crystallization from DMSO. Single-crystal X-ray diffraction analysis and ESI mass spectrometry associated with infrared multi-photon dissociation (IRMPD) tandem MS experiments confirm the formation of the large and quite stable bismuth oxido cluster 3. The reaction of compound 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 32 publications
(34 reference statements)
6
41
0
Order By: Relevance
“…However, defined intermediates formed during the hydrolysis process of 3 , as reported for Ph 2 Bi(O 3 SR) (R=phenyl, 4‐tolyl), which decompose to BiO(O 3 SR) over ten years and as reported in our previous studies on bismuth silanolates, carboxylates, and nitrates, were not observed. Therefore, [Bi 6 O 4 (OH) 4 (NO 3 ) 6 ]⋅H 2 O ( A ; approach A) and [Bi 38 O 45 (OMc) 24 (dmso) 9 (H 2 O) 2 ]⋅2 DMSO⋅5 H 2 O ( B ; approach B) were used as preorganized starting materials and were treated with 6 and 24 equivalents of vinylsulfonic acid in DMSO, respectively (Scheme ).…”
Section: Resultssupporting
confidence: 56%
“…However, defined intermediates formed during the hydrolysis process of 3 , as reported for Ph 2 Bi(O 3 SR) (R=phenyl, 4‐tolyl), which decompose to BiO(O 3 SR) over ten years and as reported in our previous studies on bismuth silanolates, carboxylates, and nitrates, were not observed. Therefore, [Bi 6 O 4 (OH) 4 (NO 3 ) 6 ]⋅H 2 O ( A ; approach A) and [Bi 38 O 45 (OMc) 24 (dmso) 9 (H 2 O) 2 ]⋅2 DMSO⋅5 H 2 O ( B ; approach B) were used as preorganized starting materials and were treated with 6 and 24 equivalents of vinylsulfonic acid in DMSO, respectively (Scheme ).…”
Section: Resultssupporting
confidence: 56%
“…Among the nuclearities observed for that ligand alone are [ Oxidoclusters supported by alkoxides, other carboxylates and hexafluoroacetylacetonate have also been reported. 7,30,31,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] They contain a core composed of Bi(III) and oxygen atoms that has an overall positive charge. These cores are then surrounded by negatively charged carboxylate ligands to form an overall neutral compound.…”
mentioning
confidence: 99%
“…The chemistry of these oxo clusters has been reviewed. 9,[11][12][13][14][15][16][17] Often when reacting bismuth halides with sodium salts of alkoxides or carboxylates, oxo-compounds are obtained. We discovered that protonolysis of BiPh 3 using acidic organic compounds can avoid the formation of oxo ligands and have applied this methodology to the production of [Bi(OC 6 F 5 ) 3 (toluene)] 2 , Bi(Hsal) 3 and various derivatives thereof.…”
mentioning
confidence: 99%